PENGARUH MOTIVASI, PENGEMBANGAN SUMBER DAYA MANUSIA DAN LOYALITAS TERHADAP KINERJA KOORDINATOR PKH PADA DIREKTORAT JAMINAN SOSIAL KEMENTERIAN SOSIAL RI - Galih Imamy Gunadi (JURNAL ILMIAH EDUNOMIKA, 2024)
This study purpose to knowing how big the influence of motivation, human resource development and loyalty to the performance of PKH Coordinators in Directorate of Social Security Ministry of Social Affairs Republic of Indonesia. The study method is quantitative method with questionnaire to 87 respondents from population of 670 people and define causal relationship. Analysis tools used is regression correlation. The first result is motivation has 30,6% significant effect on performance, the second is human resource development has 34,4% significant effect on performance, the third is loyalty has 54,7% significant effect on performance and the fourth is motivation, human resource development and loyalty they have 54,7% significant effect on performance, the effect show that between Motivation, Human Resource Development and Loyalty against performance connect a clausality mechanism relationship, which is if Motivation, Human Resource Development and Loyalty are improved or increase, that enhancement simultaneously will follow with improving performance. Key word: Motivation, Human Resource Development, Loyalty, Performance, PKH.